PENERAPAN PENDEKATAN LEARNING BY DOING DALAM MENINGKATKAN RASA KEPERCAYAAN DIRI SISWA SDN 3 TANGKILING - Norvia, Lia; Muslimah, Muslimah; Surawan, Surawan (Universitas Negeri Surabaya, 2023)
ABTRACT This study aims to determine: (1) How to apply the learning by doing approach in increasing students' self-confidence. (2) The level of student confidence when the learning by doing approach is applied. The method in this research is using mixed methods with a sample of 8 fifth grade students at SDN 3 Tangkiling who are Muslim. Monogenean data collection techniques are observations, questionnaires and interviews with data analysis using the product moment correlation formula. The results of the study show that: (1) The average application of the learning by doing approach in increasing students' self-confidence is 4.15 which is included in the high category so that the learning by doing approach is applied well. (2) The level of student confidence when the learning by doing approach is applied is 97.6% which is categorized as high. ABSTRAK Penelitian ini bertujuan untuk mengetahui: (1) Bagaimana penerapan pendekatan learning by doing dalam meningkatkan rasa kepercayaan diri siswa. (2) Tingkat kepercayaan diri siswa ketika diterapkannya pendekatan learning by doing. Adapun metode dalam penelitian ini ialah menggunakan mixed methods dengan sampel sebanyak 8 orang siswa kelas V SDN 3 Tangkiling yang beragama Islam. Teknik pengumpu lan data monogenean observasi, angket dan wawancara dengan analisis data menggunakan rumus korelasi product moment. Hasil Penelitian menunjukan bahwa: (1) Rata-rata penerapan pendekatan learning by doing dalam meningkatkan rasa kepercayaan diri siswa ialah 4.15 termasuk dalam kategori tinggi sehingga pendekatan learning by doing diterapkan dengan baik. (2) Tingkat kepercayaan diri siswa ketika diterapkannya pendekatan learning by doing ialah sebesar 97,6% yang dikategorikan tinggi.